2000
DOI: 10.1097/00002826-200001000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Treatment for Muscle Cramps: An Open-Label Trial

Abstract: To evaluate the efficacy and safety of gabapentin in the treatment of muscle cramps, we engaged an open-label trial with a group of 30 patients with frequent (> 5 cramps/week), stable, long-lasting cramps, associated with different diseases. Gabapentin was effective in reducing the frequency and severity of muscle cramps and associated sleep disturbances (clinical outcome measures) within the first 2 weeks of medication at 600 mg/d. At the 1 month control (mean dosage, 825 +/- 35 mg), almost every patient had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…A small study of multiple sclerosis patients with severe leg cramps found that 400 mg of gabapentin taken three times a day led to significant improvement in symptoms with good tolerability of the medication [35]. A follow-up study of 30 patients with frequent leg cramps and concomitant neurologic diseases such as neuropathy, radiculopathy, familial cramps, multiple sclerosis, and Parkinson's disease showed promising results [36]. Patients were started on gabapentin at 600 mg a day, and the dosage was titrated up to an average of 892 ± 180 mg a day at 3 months.…”
Section: Antiepileptic Medicationsmentioning
confidence: 99%
“…A small study of multiple sclerosis patients with severe leg cramps found that 400 mg of gabapentin taken three times a day led to significant improvement in symptoms with good tolerability of the medication [35]. A follow-up study of 30 patients with frequent leg cramps and concomitant neurologic diseases such as neuropathy, radiculopathy, familial cramps, multiple sclerosis, and Parkinson's disease showed promising results [36]. Patients were started on gabapentin at 600 mg a day, and the dosage was titrated up to an average of 892 ± 180 mg a day at 3 months.…”
Section: Antiepileptic Medicationsmentioning
confidence: 99%
“…Thirty patients treated with gabapentin for 9 months showed a decrease in frequency of cramps in an open-label, unblinded study. 30 Eight elderly patients refractory to quinine for treatment of cramps showed response to verapamil in a small open-label study. 31 A small study (n ϭ 24) of lidocaine injected directly into the calf was shown to be as effective as quinine in reducing cramps, but there are practical limitations of this mode of administration.…”
mentioning
confidence: 99%
“…Se observaron diferencias con significación estadística en la mejoría del dolor y de la intensidad de los síntomas a los 6 meses de seguimiento. Aunque no se dispone de otros trabajos que evalúen mediante EMG la eficacia de la gabapentina en el STC, Serrao et al 10 demostraron en pacientes con espasmos musculares dolorosos una mejoría por EMG a los 9 meses de tratamiento. En nuestro estudio demostramos que el EMG es una prueba complementaria que permite valorar la eficacia del tratamiento al observar estabilidad, mejoría e incluso curación en el 84,2% de los casos.…”
Section: Discussionunclassified